2019
DOI: 10.7759/cureus.5212
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocarditis Presenting as Acute Coronary Syndrome

Abstract: A 50-year-old male presented to the hospital with an approximate three-week history of nausea, fever, and back pain. Upon initial evaluation he had an electrocardiogram with ischemic changes and initial labs significant for a troponin of >25.0 ng/ml (<0.30 ng/ml), pro b-type natriuretic peptide (proBNP) of 9884 pg/ml (<125 pg/ml), and a lactic acid of 4.3 mmol/L (0.5-1.9 mmol/L). There was a concern for an acute coronary syndrome presenting as cardiogenic shock, but the patient was unable to tolerate left hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Therefore, repeatedly reviewing ECGs to observe dynamic changes and compare differences is recommended. Persistent changes in ST segments, R on T waveforms, and high degree atrioventricular blocks are suggestive of a poor prognosis [14]. Paroxysmal atrial tachycardia, low voltage of chest conduction, and severe systolic dysfunction were observed in this case report, indicating that the myocardium was damaged by the 2019-nCoV infection.…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, repeatedly reviewing ECGs to observe dynamic changes and compare differences is recommended. Persistent changes in ST segments, R on T waveforms, and high degree atrioventricular blocks are suggestive of a poor prognosis [14]. Paroxysmal atrial tachycardia, low voltage of chest conduction, and severe systolic dysfunction were observed in this case report, indicating that the myocardium was damaged by the 2019-nCoV infection.…”
Section: Discussionmentioning
confidence: 54%
“…Based on our study, all of the above-mentioned features, including young age, absence of cardiovascular risk factors, history of fever or any other infection symptoms, atypical troponin release, and an increased CRP level on admission may compose a low-risk MI patient's profile. Until now, there have been few studies sufficiently differentiating myocarditis and MI on the grounds of the non-invasive tests [9,13,17,33]. They have recommended assessment of the MI risk among young patients with ST-segment elevation before the invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The actual and accurate incidence of myocarditis in populations remains unknown, as the endomyocardial biopsy (EMB)-the diagnostic ESC gold standard-is infrequently followed in clinical practise [11,12]. It 2 of 12 is estimated that myocarditis may show the global annual prevalence of approximately 22 people for every 100,000 [13]. It is still considered a poorly understood inflammatory disease of heterogeneous manifestation caused by a variety of factors, such as infections, systemic diseases, drugs, and toxins [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Viral myocarditis is often misdiagnosed as CHD in clinical practice. In 2019, Mosebach et al reported a case of acute myocarditis presenting as an acute coronary syndrome [ 7 ]. In 2020, Tran et al studied a case of idiopathic eosinophilic myocarditis presenting with features of an acute coronary syndrome [ 8 ].…”
Section: Discussionmentioning
confidence: 99%